The architectural layout of the first Christian temples in the Kingdom of Iberia (In light of new archaeological discoveries) - Bakhtadze, Nodar (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This article is dedicated to research on the two large early Christian basilicas revealed during the last two decades on the territory of the former city of Nekresi, in Kvareli municipality, Kakheti, Georgia. Using comparative archaeological, architectural and technical analysis, the author has concluded that these basilicas were canonically designed Church buildings. As a result they must have been built by the clerical and civil rulers of the Iberian Kingdom in the second half of the 4th century and the beginning of the 5th century. It must be mentioned that even today, the majority of Georgian historians still accept the rather strange supposition elaborated by an older generation of art historians in the 1920s. According to this supposition more than a century after the recognition of Christianity as state religion, the Iberian authorities, unlike the rest of the early Christian world, built exceptionally small churches without any canonical design. Therefore, the author of this article attests to the contrary that his evidence suggests that soon after proclaiming Christianity as state religion in Georgia (in 326 AD), during the 4th century and obviously throughout the 5th century, large Churches designed in compliance with the canonical requirements of Roman and early Byzantine Christian liturgy were constructed.